Capacity of liquid steel conical tanks under hydrodynamic pressure due to horizontal ground excitations. (June 2016) - Musa, Ahmed; El Damatty, Ashraf A.
Abstract: Steel conical tanks are widely used for liquid storage around the world and especially in North America. A number of those tanks collapsed in the last decades at different places as a result of instability of the steel shells. Despite being widely used, no specific design procedure is available for conical tanks under dynamic conditions. Most of the previous studies related to steel conical tanks focused on calculating the acting forces due to a seismic event. This study however, focuses on evaluating the capacity of conical tanks under hydrodynamic pressure resulting from horizontal ground excitation using non-linear static pushover analysis. The capacity is then compared to the seismic demand obtained using a previously developed mechanical model found in the literature for different seismic zones. This paper is a part of a larger study aiming to provide a simplified design procedure for steel conical tanks when subjected to earthquakes. The study is conducted numerically using a non-linear finite element model that accounts for the effects of large deformations and geometric imperfections on the stability of steel conical tanks. Highlights: Evaluation of the capacity of steel conical tanks under hydrodynamic pressure. Inclusion of impulsive and sloshing hydrodynamic pressure components. Studding the effect of geometric imperfections on the capacity of steel conical tanks. Comparing the tank capacities to the seismic demands for different seismic zones.